Crystal structure and Hirshfeld surface analysis of aqua(1H-imidazole-κN3)[N-(2-oxidobenzylidene)threonato-κ3O,N,O′]zinc(II) - Fumishi Yoshizawa; Anna Okui; Daisuke Nakane; Takashiro Akitsu (Acta Crystallographica Section E: Crystallographic Communications)
The title complex, [Zn(C11H11NO4)(C3H4N2)(H2O)], which includes a tridentate ligand, was synthesized from L-threonine and salicylaldehyde. One water molecule and one imidazole molecule additionally coordinate the zinc(II) center in a distorted trigonal–bipyramidal geometry. The crystal structure features N—H...O and O—H...O hydrogen bonds. A Hirshfeld surface analysis indicates that the most important contributions to the packing are from H...H/H...H (50.7%) and O...H/H...O (25.0%) contacts.